Perceived health concerns among sexual minority women in Mumbai, India: an exploratory qualitative study. Issue 7 (2nd July 2016) - Bowling, Jessamyn; Dodge, Brian; Banik, Swagata; Rodriguez, Israel; Mengele, Shruta Rawat; Herbenick, Debby; Guerra-Reyes, Lucia; Sanders, Stephanie; Dange, Alpana; Anand, Vivek
Abstract: The experiences of sexual minority women (i.e., women who do not identify as 'heterosexual') in India have largely been absent in scientific literature. In partnership with India's oldest and largest sexual and gender minority-advocacy organisation, the Humsafar Trust, our study used community-based participatory research principles to explore the lived experiences and health concerns of sexual minority women in Mumbai. Study methodologies included interviews with key informants, a focus group comprised of six women, and an additional 12 in-person interviews with sexual minority women to identify important physical, mental, social and other health priorities from these women's perspectives. Thematic data are organised within the framework offered by the social ecological model, including individual, interpersonal, micro and macro levels. Findings from this study are important in providing the groundwork for future research and intervention involving sexual minority women in India, a dramatically underserved population.